The Sirenomelia Sequence: a Case Report - Sreekumar, Kavita; Fernandes, Nadia; Silveira, Maria P (Nepal Journal of Obstetrics and Gynaecology, 2017)
Sirenomelia or mermaid syndrome is a rare congenital condition with a wide phenotypic variation . It was originally named as caudal regression syndrome but it is now known that organs do not regress, they just do not form. An abnormal abdominal and umbilical vascular arrangement of affected individuals, and a primary abnormality in the generation of the mesoderm are two theories suggested for its genesis.  Affected individuals show hypoplastic and fused lower limbs, vertebral abnormalities, and agenesis of the renal system, imperforated anus, and genital organs anomalies. Antenatal diagnosis in the first trimester is critical. We report a case of the mermaid syndrome associated with severe oligohydramnios, Potter’s facies, unilateral renal agenesis, and absent external genitalia.